Historical Background of Islamic Education Modernization - Fatima Rahma Rangkuti (Cipta Pustaka Nusantara, 2026)
This study examines the historical background of Islamic education modernization from the seventeenth to the nineteenth century by using a historical approach grounded in library research. Drawing on documentary and bibliographic sources, the study analyzes four dimensions: the epistemological narrowing of Islamic education in the seventeenth and eighteenth centuries, the intellectual and institutional advancement of the West, the disruptive effects of colonialism on Muslim societies, and the emergence of modernization consciousness among Muslims. The findings show that the crisis of Islamic education was not a total decline, but a narrowing of curriculum, pedagogy, and intellectual inquiry that weakened the balance between memorization, reasoning, and integrative learning. At the same time, Western scientific progress, political power, and colonial expansion exposed the limitations of inherited educational structures and accelerated reformist responses across the Muslim world. The study finds that modernization in Islamic education emerged not as imitation of the West, but as a selective process of renewal aimed at restoring intellectual vitality, institutional relevance, and civilizational agency while remaining grounded in Islamic values. These findings imply that Islamic education should approach modernization as critical reconstruction rather than unreflective Westernization, integrating religious foundations with broader intellectual and social demands in educational practice.